2019
DOI: 10.1038/s41598-019-40859-1
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae autoinducer-1 enhances the virulence of enteropathogenic Escherichia coli

Abstract: Diarrhoea is the second leading cause of death in children under the age of five. The bacterial species, Vibrio cholerae and enteropathogenic Escherichia coli (EPEC), are among the main pathogens that cause diarrhoeal diseases, which are associated with high mortality rates. These two pathogens have a common infection site—the small intestine. While it is known that both pathogens utilize quorum sensing (QS) to determine their population size, it is not yet clear whether potential bacterial competitors can als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 65 publications
(90 reference statements)
0
18
0
Order By: Relevance
“…A recent study showed that some non-01/O139 V. cholerae (NOVC) strains also cause diarrhea ( Vezzulli et al., 2020 ). V. cholerae can also affect the virulence of pathogenic Escherichia coli , and the virulence of EPEC is enhanced with the elevated concentration of cholera autoinducer 1 (CAT-1) when grown in co-culture with V. cholerae ( Gorelik et al., 2019 ).…”
Section: Gut Microbiota-mediated Diarrhea and Its Mechanismmentioning
confidence: 99%
“…A recent study showed that some non-01/O139 V. cholerae (NOVC) strains also cause diarrhea ( Vezzulli et al., 2020 ). V. cholerae can also affect the virulence of pathogenic Escherichia coli , and the virulence of EPEC is enhanced with the elevated concentration of cholera autoinducer 1 (CAT-1) when grown in co-culture with V. cholerae ( Gorelik et al., 2019 ).…”
Section: Gut Microbiota-mediated Diarrhea and Its Mechanismmentioning
confidence: 99%
“…For instance, diarrhoea is one of the leading causes of high mortality rates in children under 5 years of age. It is caused mainly by Vibrio cholerae and E. coli (EPEC) 148 which utilize quorum sensing (an intercellular communication process) to determine their own population size. During the period of colony formation, the biofilm grows by division of existing cells and, furthermore, by attracting other microorganisms.…”
Section: Sers-based Pathogen Detection Methodsmentioning
confidence: 99%
“…241 Copyright 2019, American Chemical Society. 150 autoinducers, 148 pyocyanin-like byproducts 243 or mitochondrial activity indicators. Much less attention has been devoted to the extracellular products released by bacteria, in the matrix surrounding the biofilms.…”
Section: Sers-based Methods For Bacterial Infection and Disease Diagnosismentioning
confidence: 99%
“…89 While long thought to be specific to Vibrios, recent work has demonstrated that pathogenic E. coli are also able to sense this autoinducer. 90 CAI-1 levels are monitored by the membrane-bound histidine kinase sensor CqsS, 91 which acts as a kinase at low cell-and AI-density, auto phosphorylating and transferring this phosphate to LuxU and thence to the regulator LuxO, leading to Qrr sRNA expression and the upregulation of aphA and repression of hapR. At high cell density and thus high CAI-1 concentrations, CAI-1 binds to CqsS converting it from kinase to phosphatase activity, leading to the dephosphorylation of LuxO.…”
Section: Quorum Sensing the Gut Microbiome And V Cholerae Pathogenesismentioning
confidence: 99%